Perception vs action: the computations may be the same but the direction of fit differs - Shea, N (Cambridge University Press, 2013)
Although predictive coding may offer a computational principle that unifies perception and action, states with different directions of fit are involved (with indicative and imperative contents, respectively). Predictive states are adjusted to fit the world in the course of perception, but in the case of action the corresponding states act as a fixed target towards which the agent adjusts the world.